2005
DOI: 10.1152/ajpregu.00828.2004
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle responses elicited by dorsal periaqueductal gray stimulation in rats

Abstract: The periaqueductal gray matter is an essential neural substrate for central integration of defense behavior and accompanied autonomic responses. The dorsal half of the periaqueductal gray matter (dPAG) is also involved in mediating emotional responses of anxiety and fear, psychological states that often are associated with changes in ventilation. However, information regarding respiratory modulation elicited from this structure is limited. The present study was undertaken to investigate the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Electrical or chemical stimulation of the dPAG is known to evoke significant increases in blood pressure and HR [3,6,14,21,43,73]. In contrast, vPAG stimulation induces depressant effects, such as lowered blood pressure and HR, coupled with immobility [3,6,14].…”
Section: Discussionmentioning
confidence: 99%
“…Electrical or chemical stimulation of the dPAG is known to evoke significant increases in blood pressure and HR [3,6,14,21,43,73]. In contrast, vPAG stimulation induces depressant effects, such as lowered blood pressure and HR, coupled with immobility [3,6,14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, none of these studies explores stereotaxically the influence of different areas of the PAG on respiratory function. Subramanian et al (2007Subramanian et al ( , 2008 studied the PAG-induced changes to caudal medullary respiration-related neuronal activity in the rat, and Huang et al (2000) also in the rat investigated the role of the PAG on cardiorespiratory control, and subsequently Hayward et al (2003Hayward et al ( , 2004 and Zhang et al (2005Zhang et al ( , 2007 examined the PAGinduced change to respiratory frequency. However, all these studies in the rat focused on the dorsal PAG and reported only excitatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies (Magoun et al, 1937;Bandler and Carrive, 1988;Zhang et al, 1994;Nonaka et al, 1999;Nakazawa et al, 2000), the sound production was measured but not the respiratory function. In the rat, a few studies exist (Huang et al, 2000;Hayward et al, 2003Hayward et al, , 2004Zhang et al, 2005Zhang et al, , 2007Subramanian et al, 2007Subramanian et al, , 2008, but they were limited to the dorsal PAG showing only an increase in respiratory frequency. The present study is the first that investigated the PAG effects on respiration by stimulation of different parts of the PAG.…”
Section: Introductionmentioning
confidence: 99%
“…Under "resting" conditions (i.e. normoxic-normocapnia) electrical and chemical stimulation of dorsal PAG (dPAG) increase ventilation in both cats and rats (Bassal and Bianchi, 1982;Duffin and Hockman, 1972;Hayward and Castellanos, 2004;Hayward et al, 2003;Hockman et al, 1974;Huang et al, 2000;Lovick, 1985;Zhang et al, 2005). However, the recent demonstration that focal lesions in the dlPAG/dmPAG does not alter ventilation during normocapnia, suggests that this area does not exert a tonic influence on respiratory control at rest but may be activated in specific situations (Lopes et al, 2012).…”
Section: The Periaqueductal Gray and Respiratory Controlmentioning
confidence: 99%